The role of high-performance sport environments in mental health: an international society of sport psychology consensus statement - Henriksen, K.; Huang, Z.; Bartley, J.; Kenttä, G.; Purcell, R.; Wagstaff, C. R. D.; Si, G.; Ge, Y.; Schinke, R. (International Journal of Sport and Exercise Psychology, 2025)
This consensus statement is the product of the Third International Society of Sport Psychology Think Tank on Mental Health. The purposes of the Think Tank were (1) to engage renowned international expert researchers and practitioners in a discussion about the role of high-performance sport environments in nourishing or malnourishing the mental health of athletes, coaches and staff; and (2) to develop recommendations for sport organisations, mental health researchers, and practitioners to more fully recognise the role of the sport environment in their work. Although most of the research on mental health in sport has focused on the individual, mental health is the result of intricate and dynamic relationships between people and their environments, and a range of stakeholder individuals and organisations play a key role in supporting wellbeing in high-performance sport. We conceptually divide the environment into three levels (the sport team, sport organisation and sport system) and two dimensions (the social and the physical environment). Based on the portraits of these environments, we conclude by providing recommendations that will help sport teams, organisations, and systems to create nourishing high-performance sport environments and effective mental health service provision environments, whilst helping researchers expand their focus from the individual athlete or coach to the sport environment.